KEBIJAKAN TRANSPORTASI PEMERINTAH KOTA PADANG DALAM MENGATASI KEMACETAN LALU LINTAS DI KAWASAN BUNDARAN AIR MANCUR PASAR RAYA PADANG - Dewi Dahlan (IAIN Batusangkar, 2019)
Density of traffic is increasing very quickly in Indonesia ending of the time and that’s problem making serious of traffic Jam. One of city experience that is Padang. One of the area experience that traffic is Bundaran air Mancur, Pasar Raya Padang. This research destination is to know and to description Padang Governmental to overcoming traffic Jam in Bundaran Air Mancur, Pasar Raya Padang. Location of this thesis is Bundaran Air Mancur, Pasar Raya Padang, using qualitative and descriptive method, and purposive sampling to choice the informan. This thesis using 8 method books, 19 theory books, 5 of journal and 8 websites. If we hooked the problem with aspect of transportation like Le Grand, Julian and Ray Robinson said in their book they said that four aspects of transportation to look city of transportation is availability, quality, accessibility, and price then Padang Governmental already take out some policy but that policy not yet to support aspect of transportation. From the result of this research can we make conclution that legitimate policy take out of Padang Governmental in just in sector price. Other aspect like availability, accessibility and quality not yet to be serious attention by taker of policy of transportation. Padang Governmental give autonomy for Communication Department to put in order operational transportation problems in Padang City included in Bundaran Air Mancur be based on Padang Mayor Regulation Number 31 years 2008, where Communication Department posess one of task to manage and traffic engineer. By based on that Communication Department have knit some special policy without Mayor and Indonesian Legislation Assembly agreement. Policy take out by Communication Depatment to solve traffic Jam in Bundaran Air Mancur is canalisation system.